Surveys of African economies : the Gambia, Ghana, Liberia, Nigeria, and Sierra Leone - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1975)
This volume covers five English-speaking countries - The Gambia, Ghana, Liberia, Nigeria, and Sierra Leone - situated on the west coast of Africa. The volume is based mainly on published sources, supplemented by data gathered by Fund missions from the central banks and national authorities, who have authorized their publications.
Includes bibliographical references.
Loans
rpm 06/04/2017
Keywords: Economic conditions; Finance; Africa